Born to be Sold: Start-ups as Products and New Territorial Life Cycles of Industrialization - Livi, Christian; Jeannerat, Hugues (My University, 2014)
Territorial innovation models and policy practices traditionally tend to associate the emergence, resurgence and growth of start-ups with the development of local industries, either as industrial pioneers or as innovative spinoffs embedded in a regional production system. This approach is in line with a “life cycle” pattern of innovation and of industrialization marked by sequential waves of growth and decline, by technological renewal and by sectorial transitions. In a knowledge and financial economy characterized by combinatorial knowledge dynamics, by even shorter project-based innovations and by global financial and production networks, this approach is called into question. Through the case of Swiss medical technologies (Medtech), this paper highlights how local medtech start-ups' evolution is shaped, from its early phase on, by the corporate venture strategies of multinational companies. While the economic potential of start-ups was traditionally perceived in a longer run, they seem to be more often “born to be sold” today. New research avenues and policy issues are finally derived from this particular case to address territorial innovation and competitiveness in the future.